Main factors affecting the efficacy of medicinal plants during the cultivation process - Zhang, Chunhong; Zhong, Xuejing; Bao, Saqirula; Urtnasan, Myadagbadam; Li, Minhui (Frontiers in Plant Science, 2025)
The escalating global demand for safe and efficacious traditional Chinese medicine (TCM) has underscored the urgent need for a stable and high-quality supply of medicinal plant resources. While large-scale cultivation offers a practical solution to alleviate the pressure on wild populations, ensuring the consistent expression of active secondary metabolites and reproducible pharmacological efficacy remains a central challenge. The biosynthesis and accumulation of these bioactive compounds are governed by a complex interplay of factors spanning all stages of cultivation and post-harvest handling. This narrative review systematically analyzes and identifies from current literature the five key dimensions influencing the therapeutic efficacy of medicinal plants: (1) production area selection, where ecological suitability shapes plant metabolic responses; (2) genetic resources, which determine the biosynthetic potential of active constituents; (3) field management practices, including nutrient regulation and cropping systems; (4) the control methods of diseases, insect pests, and weeds, integrating ecological approaches with rational chemical use to reduce residues and ensure safety; and (5) harvesting, processing, and storage techniques, which affect the stability and bioavailability of bioactive compounds. These interconnected factors collectively determine the final quality and therapeutic efficacy of medicinal plant raw materials. Coordinated management of these five dimensions is essential for establishing standardized, ecologically sustainable cultivation systems, which are crucial for ensuring quality assurance, enhancing supply chain resilience, and promoting the modernization and global recognition of TCM. This review offers a comprehensive theoretical and technical framework to guide the development of efficient medicinal plant production systems yielding materials with consistent efficacy and safety.